Correlation Between the Sagittal Skeletal Relationship and Lower Anterior Facial Height - A Retrospective Study - MALIAEL, DR. MATHEW THOMAS; KUMAR, DR.M. NAVEEN (The journal of contemporary issues in business and government, 2021)
This investigation aimed to study and evaluate the correlation between the Sagittal Skeletal Relationship and the Lower Anterior Facial Height. A single-center data collection was done. 490 Lateral Cepahalograms were collected and traced. Only adult patients with average were considered for the study. 31 cephalograms were included. Beta angle measurement was used to divide the cephalograms into 3 groups. The lower anterior facial height measurement was made for each cephalogram. The Data was tabulated into an MS Excel spreadsheet. One Way ANOVA analysis was performed to study the correlation between the groups. The average Lower anterior facial height for all the groups 68.47 ± 11.3 mm. The significance derived from the ANOVA test is 0.762. No statistically significant correlation between the Sagittal Skeletal Relationship and Lower Anterior Facial Height in the south Indian population